Poverty As a Catalyst for Migration and International Asylum: An Analytical Study of Turkey's Experience for The Period (2010–2023) - Miklif, Dr. Huda Zwair (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Poverty and forced migration represent intertwined global development challenges affecting host-country stability. Specific Background: Turkey has become the world’s largest refugee-hosting country amid rising poverty pressures since 2010. Knowledge Gap: Empirical evidence on the long- and short-term dynamics between poverty and international asylum in Turkey remains limited. Aims: This study analyzes the poverty–asylum relationship during 2010–2023 using an ARDL approach. Results: Findings reveal a significant long-term inverse relationship, with weak short-term effects. Novelty: The study integrates poverty and asylum within a unified econometric framework linked to SDGs. Implications: Effective policy requires coordinated poverty reduction and refugee integration strategies.Highlight : A long-term inverse relationship exists between poverty rates and refugee numbers in Turkey. The short-term relationship between poverty and asylum is weak and statistically insignificant. The results underscore the importance of integrated policies aligned with SDG 1 and SDG 10. Keywords : Poverty, International Asylum, Turkish Economy, ARDL Model, Sustainable Development